2010
DOI: 10.1016/j.jmb.2010.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Elements at Both Cytoplasmically and Extracellularly Facing Sides of the UapA Transporter Selectively Control the Accessibility of Substrates to Their Translocation Pathway

Abstract: In the UapA uric acid-xanthine permease of Aspergillus nidulans, subtle interactions between key residues of the putative substrate binding pocket, located in the TMS8-TMS9 loop (where TMS is transmembrane segment), and a specificity filter, implicating residues in TMS12 and the TMS1-TMS2 loop, are critical for function and specificity. By using a strain lacking all transporters involved in adenine uptake (DeltaazgA DeltafcyB DeltauapC) and carrying a mutation that partially inactivates the UapA specificity fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 34 publications
3
55
0
12
Order By: Relevance
“…It is interesting to note that Thr-280 and, especially, Ala-279 display a high degree of conservation among members of the NAT/NCS2 family (5,10) and that Ala-363, the residue corresponding to Ala-279 in the fungal homolog UapA (5), has been suggested as critical for function in Aspergillus nidulans, based on the loss-of-function phenotype of mutant A363D (18). Although a more comprehensive mutagenesis study of Ala-363 is missing (5,6), genetic analysis has shown that presence of a Gly in place of Ala-363 is compatible with full UapA activity (18), which is reminiscent of the wild-type expression and activity seen with mutant A279G in YgfO (Fig. 6).…”
Section: Table 2 Specificity Profile Of Mutant D276ementioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that Thr-280 and, especially, Ala-279 display a high degree of conservation among members of the NAT/NCS2 family (5,10) and that Ala-363, the residue corresponding to Ala-279 in the fungal homolog UapA (5), has been suggested as critical for function in Aspergillus nidulans, based on the loss-of-function phenotype of mutant A363D (18). Although a more comprehensive mutagenesis study of Ala-363 is missing (5,6), genetic analysis has shown that presence of a Gly in place of Ala-363 is compatible with full UapA activity (18), which is reminiscent of the wild-type expression and activity seen with mutant A279G in YgfO (Fig. 6).…”
Section: Table 2 Specificity Profile Of Mutant D276ementioning
confidence: 99%
“…More than 1,000 sequence entries are known but few are functionally characterized to date. Structure-function relationships have been studied extensively in two members, the eukaryotic UapA, a high-affinity uric acid/xanthine:H ϩ symporter from the ascomycote Aspergillus nidulans (3)(4)(5)(6) and the prokaryotic YgfO, a specific, high-affinity xanthine:H ϩ symporter from Escherichia coli (7)(8)(9)(10)(11). Mutagenesis data from both lines of study have shown that key NAT determinants are strikingly similar between the two transporters, and that few residues conserved throughout the family may be invariably critical for function (10).…”
mentioning
confidence: 99%
“…Homology modeling shows that most of the residues identified as important in both XanQ (7)(8)(9) and UapA (11)(12)(13)(14) fall in TM1, TM3, TM8, and the NAT-signature motif (TM10) and are either in the putative binding site or at the periphery forming a shelter around substrate in the core domain of the protein (supplemental Fig. S1).…”
mentioning
confidence: 99%
“…These residues are probably crucial in defining the molecular basis of NAT substrate recognition and selectivity. In addition, more dynamic structural elements located in the gate domain (1) may contribute to affinity and specificity by controlling access of substrates to the binding site and implementing the appropriate conformational changes; the current genetic and biochemical evidence on UapA (12)(13)(14) and XanQ (6) suggests that residues involved in such gating mechanisms are found in the last transmembrane segment (TM14) (6,12,13), in cytoplasmic loop TM12-TM13 (13) and in sequence regions flanking TM1 (13,14).…”
mentioning
confidence: 99%
“…With respect to function, only 15 of more than 2,000 predicted members have been characterized in detail; these are specific for the cellular uptake of uracil, xanthine, or uric acid (microbial, plant, and nonprimate mammalian genomes) or vitamin C (mammalian genomes) (1)(2)(3). Two of them, the xanthine permease XanQ of Escherichia coli (4 -10) and the uric acid/xanthine permease UapA of Aspergillus nidulans (11)(12)(13)(14)(15), have been studied extensively with Cysscanning mutagenesis and reverse and forward genetics, respectively. These studies have shown striking similarities between key NAT determinants of the two transporters, reinforcing the idea that few residues at conserved motifs of the family may be invariably critical for function or underlie specificity differences (for a summary of current knowledge, see supplemental Fig.…”
mentioning
confidence: 99%